2019
DOI: 10.1002/kjm2.12146
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of mitochondrial unfolded protein response contribute to resistance declination of H2O2‐induced injury in senescent MRC‐5 cell model

Abstract: Accumulation of oxidative proteins within mitochondria leads to loss of mitochondrial function, which may lead to age-related degenerative diseases. Mitochondrial antioxidant defense capacity reflects the expression of mitochondrial unfolded protein response (mtUPR)-related proteins. Senescent cells are considered to be less resistant to cellular stress stimuli than exponentially growing cells. In this study, we aimed to investigate the ability of mitochondrial stress response in senescent cells to cope with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The common notion is that there is an increase in the intracellular Ca 2+ during senescence progression. It has been reported that a higher Ca 2+ concentration in replicative senescent fibroblasts was noted compared to that in nonsenescent cells [49]. Another research demonstrated that rotenone-induced premature senescence in human neuroblastoma cells was accompanied with cytosolic Ca 2+ rise [50].…”
Section: Discussionmentioning
confidence: 96%
“…The common notion is that there is an increase in the intracellular Ca 2+ during senescence progression. It has been reported that a higher Ca 2+ concentration in replicative senescent fibroblasts was noted compared to that in nonsenescent cells [49]. Another research demonstrated that rotenone-induced premature senescence in human neuroblastoma cells was accompanied with cytosolic Ca 2+ rise [50].…”
Section: Discussionmentioning
confidence: 96%
“…In senescent hepatocytes, most of the UPRmt factors levels were found significantly reduced and the pathway compromised [ 108 ], suggesting that UPRmt targeting could have a role in preventing senescence. Similarly, experiments in senescent human lung fibroblasts showed a reduced ability to cope with the accumulation of mitochondrial unfolded proteins [ 109 ]. Additional research is needed to investigate this hypothesis.…”
Section: Mitochondrial Unfolded Protein Responsementioning
confidence: 99%